4, 5‐Bis(5‐tetrazolyl)‐1, 2, 3‐triazole: Synthesis and Performance. Issue 6 (13th October 2015) - Du, Zhiming; Zhang, Yinghao; Han, Zhiyue; Yao, Qian
Abstract: 4, 5‐Bis(5‐tetrazolyl)‐1, 2, 3‐triazole (BTT) was synthesized by a new method. Its structure was characterized by IR and 13 C NMR spectroscopy and elemental analysis (EA). The thermal stability of BTT was investigated by TG‐DSC technique. The kinetic parameters including activation energy and pro‐exponential factor were calculated by Kissinger equation. The combustion heat, detonation products, hygroscopicity, impact, and friction sensitivity were also measured. The formation heat, detonation pressure, and detonation velocity of BTT were calculated. BTT has high detonation pressure and detonation velocity ( P =35.36 GPa, D =8.971 km s −1 ). BTT has potential application prospect as environmentally friendly gas generant, insensitive explosive and solid propellant. Abstract :